ANALYSIS PLANNING AND DESIGN STRUCTURE OF BUILDING FLATS RENT FOR FACTORY WORKERS IN INDUSTRIAL AREA CIREBON REGENCY - Nurrohman, Taufik; Rohman, Fathur (Journal of Green Science and Technology, 2019)
ABSTRACTThe industrial area in Cirebon Regency which has absorbed a number of industrial workers need to be supported by the infrastructure that facilitates the existence of industrial workers from inside and outside of Cirebon Regency, namely is residence that becomes one of the primary needs / basic human and they should find a place to live that suits the needs and financial capabilities. According to the Constitution 1945, Law No. 4 1992 Housing and Settlement and the Law No. 39 of 1999 on Human Rights, the house is the people's basic rights and guaranteed by law and supported by the Presidential Decree 22/2006 issued a national program "Flats 1000 Tower" which was targeted to build flats are middle to lower class.In order to create a structure that is safe and meets serviceability limit, so in the process of design the building structure must be according to SNI 2847-2013 of reinforced concrete. Beside planning, the loading structure must be according to SNI 1727-2013, then for calculation of earthquake engineering refers to SNI 1726-2012. Analysis structure using ETABS, for the material of structures is used concrete including frame section (column, sloof, beam, and slab).From the planning and design of the flats that were done in this thesis obtained 2 types of columns with a size 50/50 using reinforcement 12-D19 and shear reinforcement ?10-100 and 35/35 using reinforcement 8-D19 and shear reinforcement ?10-100, then obtained 2 types of main beams with a size 35/50 using reinforcement 12-D16 with shear reinforcement ?10-100 and size 25/30 using reinforcement 5-D16 with shear reinforcement ?10-120, then for floor and roof slab obtained a thickness 13cm using reinforcement D12-150. RAB structure obtained in this plan is Rp.15,920,000,000,- so that the price per meter is Rp.3,686,000,-.Keywords : Analysis and Planning structure, ETABS, Thesis Result.